A knowledge, attitude and practice study of evidence-based nursing combined with narrative nursing mode to improve the quality of life of glioma patients - Weng, Jiehui; Ma, Lihong; Li, Jianrong; Zhu, Li; Fang, Yanwei (Frontiers in Medicine, 2025)
BackgroundExisting nursing knowledge-attitude-practice (KAP) studies have mostly focused on a single model of evidence-based nursing (EBN) or narrative nursing (NN) rather than an integrative approach. Meanwhile factors influencing nurses’ KAP in glioma care scenarios have not been studied. These gaps hinder the translation of evidence-based and narrative nursing integration into clinical practice and limit the improvement of patient prognosis.MethodsThe knowledge-attitude-practice online questionnaire for nurses included the EBN knowledge questionnaire and NN cognitive assessment. Structural equation modeling was used to analyze the path relationships between knowledge, attitude, and practice. Pearson correlation coefficient was employed to explore the correlations among knowledge, attitude, and practice. Multivariate logistic regression analysis was conducted to examine the impact of demographic factors on the knowledge-attitude-practice levels of nurses. The quality of life of glioma patients was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire.ResultsA total of 164 nurses and 352 glioma patients were included in the study. Significant differences in the three knowledge-attitude-practice dimensions of nurses were found based on age, length of work, education background and job title. Professional knowledge played a central role in the construction of attitudes and the transformation of behaviors in nurses. A strong positive correlation was observed between knowledge and practice (r = 0.837), while a moderate positive correlation existed between attitude and both knowledge (r = 0.481) and practice (r = 0.499). Nurses with higher job title (head nurse) performed better in terms of attitude. The impact of education level on the three knowledge-attitude-practice dimensions was relatively small. Additionally, the overall functional status of glioma patients was good (median = 86 points, Q1 = 70.93, Q3 = 95), there was a significant difference in health status (median = 66.7 points, Q1 = 50, Q3 = 83.3), while the difference in symptom severity was relatively small (median = 11.11 points, Q1 = 3.7, Q3 = 24.69).ConclusionThe knowledge-attitude-practice levels of nurses on EBN and NN are influenced by their own background factors, with professional knowledge playing a crucial role in shaping their attitude and behavior transformation, which may help in developing targeted educational interventions and effective public health strategies for glioma patients.